Predicting Active Shooter Events: Are Regional Homogeneity, Intolerance, Dull Lives, and More Guns Enough Deterrence?. (August 2019) - Duque, Richard B.; LeBlanc, E.J.; Rivera, Robert
Based upon a secondary analysis of 2016 General Social Survey (GSS) data, this study identifies regional "Heterogeneity", "Tolerance", "Life is Exciting", "Lack of Confidence in Institutions" and "Gun Ownership" effects related to the frequency of Active Shooter events, which occured in the United States between 2000 to 2016. For Education Active Shooters, regional homogeneity is related to more tragic events as is less gun ownership per capita. For Workplace Active Shooters, more gun ownership per capita is associated with more events as is regional diversity and tolerance. The findings support calls for arming schools in white, affluent neighborhoods as well as more aggressively profiling, arresting and convicting potential White perpetrators in order to reduce the risk of Education Active Shooters. Meanwhile, stronger gun control measures in diverse and tolerant regions might reduce the incidents of Workplace Active Shooter events. The findings also suggest that organizations should acquire digital "Human Analytics" platforms and programs that integrate internal member profiles, conflict incident reports and culture climate data along with relevant regional and national data like that analyzed in this paper to help alert them to their dynamic Active Shooter risk. Also, re-evaluating diversity training seminars and courses, which often cast teen and middle-aged, White males as historical "villains", might help address the chronic strain this population experiences at school and at work. Finally, re-evaluating how disassociated White males are treated, as well as expelled/fired from school or work, might also help defuse the "popcorn effect"associated with these tragic events.